Rapid emergence of multidrug resistant, H58-lineage Salmonella typhi in Blantyre, Malawi. - Nicholas A Feasey; Katherine Gaskell; Vanessa Wong; Chisomo Msefula; George Selemani; Save Kumwenda; Theresa J Allain; Jane Mallewa; Neil Kennedy; Aisleen Bennett; Joram O Nyirongo; Patience A Nyondo; et al. (PLoS Neglected Tropical Diseases)
Introduction Between 1998 and 2010, S. Typhi was an uncommon cause of bloodstream infection (BSI) in Blantyre, Malawi and it was usually susceptible to first-line antimicrobial therapy. In 2011 an increase in a multidrug resistant (MDR) strain was detected through routine bacteriological surveillance conducted at Queen Elizabeth Central Hospital (QECH). Methods Longitudinal trends in culture-confirmed Typhoid admissions at QECH were described between 1998-2014. A retrospective review of patient cases notes was conducted, focusing on clinical presentation, prevalence of HIV and case-fatality. Isolates of S. Typhi were sequenced and the phylogeny of Typhoid in Blantyre was reconstructed and placed in a global context. Results Between 1998-2010, there were a mean of 14 microbiological diagnoses of Typhoid/year at QECH, of which 6.8% were MDR. This increased to 67 in 2011 and 782 in 2014 at which time 97% were MDR. The disease predominantly affected children and young adults (median age 11 [IQR 6-21] in 2014). The prevalence of HIV in adult patients was 16.7% [8/48], similar to that of the general population (17.8%). Overall, the case fatality rate was 2.5% (3/94). Complications included anaemia, myocarditis, pneumonia and intestinal perforation. 112 isolates were sequenced and the phylogeny demonstrated the introduction and clonal expansion of the H58 lineage of S. Typhi. Conclusions Since 2011, there has been a rapid increase in the incidence of multidrug resistant, H58-lineage Typhoid in Blantyre. This is one of a number of reports of the re-emergence of Typhoid in Southern and Eastern Africa. There is an urgent need to understand the reservoirs and transmission of disease and how to arrest this regional increase.